New molecularly targeted therapies for lung cancer - Sun, Sophie; Schiller, Joan H.; Spinola, Monica; Minna, John D. (The Journal of Clinical Investigation, 2007)
Lung cancer is the leading cause of cancer death worldwide. The disease is particularly difficult to detect, and patients often present at an advanced stage. Current treatments have limited effectiveness, and unfortunately, the prognosis remains poor. Recent insights into the molecular pathogenesis and biologic behavior of lung cancer have led to the development of rationally designed methods of early detection, prevention, and treatment of this disease. This article will review the important clinical implications of these advances, with a focus on new molecularly targeted therapies currently in development.